Propuesta de plan de marketing con soporte en las TIC´S para la cooperativa de ahorro y crédito COACMES de San Jacinto - Moreira Saltos, Stefany Jazmín (2019)
The main objective of this research was a marketing plan with support in ICT for the savings and credit cooperative of San Jacinto. To achieve this, the research comprised three methodological phases: (1) analysis of the current situation of the cooperative, through the application of an interview to the manager of the entity, survey of partners, analysis of pests, five forces of transport and analysis SWOT (2) formulation of strategic objectives, through the action plan 5w + 1h; (3) the preparation of the marketing plan, the compilation of the distribution plan, the sale and advertising, and finally the preparation of the budget. The results determine that the main shortcomings related to the cooperative are related to the marketing process, mainly in the lack of advertising channels and the lack of incorporation of ICT in the marketing process, so the plan of an intensive action , through various means of communication; develop a database with complete information on financial operations; train personnel on customer service, the use of ICT and the management of financial services.